Promoting Energy Efficiency in the Building Sector as A Mechanism for Mainstreaming Sustainable Development Survey of the Residential Sector in Algeria 2000-2017 - Hadda, Rebbouh; Bendjeroua, Hakim; Mekhelfi, Amina (جامعة حسيبة بن بوعلي الشلف - مخبر تنمية تنافسية المؤسسات الصغيرة والمتوسطة الجزائرية في الصناعات المحلية البديلة, 2020)
تختلف نسب استهلاك الطاقة في العالم بين مختلف القطاعات ويمثل قطاع المباني نسبة 40 % من الطاقة المستهلكة سنويا في العالم، ونظرا لارتفاع نسب الاستهلاك العالمي في الطاقة تم بذل جهود متنوعة في تطوير السياسات الهادفة لتشجيع فعالية الطاقة بالعالم، ومنه تهدف هذه الدراسة إلى تقديم نظرة عامة حول سياسات وإجراءات تشجيع فعالية الطاقة بالعالم مع التركيز على حالة الجزائر من خلال اعتماد المنهج الوصفي التحليلي استنادا على مجموعة وثائق صادرة عن الهيئات الحكومية الجزائرية كوزارة الطاقة، الوكالة الوطنية لترشيد وترقية استخدام الطاقة وذلك بتحليل واقع استهلاك الطاقة في قطاع السكنات بالجزائر والسياسة التي اعتمدتها الجزائر في مجال فعالية الطاقة قصد تحقيق أهداف التنمية المستدامة، وقد خلصت الدراسة إلى أن هناك العديد من العراقيل التي تقف وراء تطوير فعالية الطاقة في قطاع المباني، وعلى الجزائر بذل المزيد من الجهود من أجل التنفيذ الحقيقي والفعلي للبرامج المدرجة.
World energy consumption rates vary among different sectors and the building sector accounts for 40% of the world's energy consumption annually, and due to the high world energy consumption rates, various efforts have been made to develop policies to promote energy efficiency in the world, and from wich this study aims to provide an overview of policies and measures to promote energy efficiency in the world, focusing on the situation of Algeria by adopting a descriptive analytical approach based on a set of documents issued by the Algerian government agencies, such as the Ministry of Energy, the National Agency for the Conservation and Promotion of Energy Use, by analysing the energy efficiency policy adopted by Algeria to achieve the objectives of sustainable development. The study concluded that there are many obstacles that stand in the development of energy efficiency in the buildings sector, and that Algeria should exert more efforts for real and effective implementation of the listed programs.
Keywords: التنمية المستدامة -- القطاع السكني -- الجزائر